Efficacy of parent-mediated communication-focused treatment in toddlers with autism (PACT) delivered via videoconferencing: a randomised controlled trial study protocol. Issue 4 (7th April 2021) - Jurek, Lucie; Occelli, Pauline; Denis, Angelique; Amestoy, Anouck; Maffre, Thierry; Dauchez, Tom; Oreve, Marie-Joelle; Baghdadli, Amaria; Schroder, Carmen; Jay, Agathe; Zelmar, Amélie; Revah-Levy, Anne; et al.
Abstract : Introduction: Intervention in the preschool period is currently recommended for autism spectrum disorder. Therapies delivered by parents are particularly suitable for young children. Preschool Autism Communication Trial (PACT) is a parent-mediated therapy that has shown a significant and sustained impact on autism symptom reduction. However, access to such evidence-based therapies for families is limited due to autism centres located in large urban areas. Using videoconferencing to deliver PACT training to parents may improve accessibility for families living in underserved areas. Methods and analysis: This single-blind randomised controlled trial, involving six sites in France, will investigate the efficacy of a telehealth, videoconferencing-based, parent-mediated PACT therapy on autism symptoms, over a 12-month period. It will compare PACT plus treatment as usual (TAU) against TAU only in a cohort of 238 toddlers (119 per group) aged 18–36 months at inclusion and living with their families more than 40 min away from the specialist centres for autism. Primary outcome will include change of overall autism score on the Autism Diagnostic Observation Scale (ADOS) at 12 months. Secondary outcomes will measure change in child skills, child functioning, impact on parents (stress, health, priorities) and implementation characteristics. Repeated measures analyses will be used to test the effect of PACT intervention on the overall ADOS module 1 score over the 12-month study period. Linear mixed models will be used with time, treatment allocation and the interaction between treatment and time as fixed effects and individual variation as random effect. Ethics and dissemination: This protocol (V.5, date: 25 October 2019) is approved by the French National Review Board (reference no 2018-A02516-49). The results will be disseminated via peer-reviewed journals Trial registration number: NCT04244721 .